Polysulfone/iron oxide nanoparticles ultrafiltration membrane for adsorptive removal of phosphate from aqueous solution - Abidin, M. N. Z. (Amirkabir University of Technology - Membrane Processes Research Laboratory, 2019)
Excessive nutrient contents in water bodies renders eutrophication and causes undesired structural changes to the environment. One of the most straightforward strategies to address eutrophication issue is through the removal of nutrients such as phosphate ions from the water sources. A combination of membrane filtration and adsorption process is an attractive alternative to remove phosphate from aqueous solution. In this work, polysulfone/iron oxide nanoparticles (PSf/IONPs) adsorptive nanocomposite ultrafiltration (UF) membrane was prepared via phase separation process. Flat sheet membranes were characterized using scanning electron microscopy, energy-dispersive X-ray spectrometry, contact angle, overall pore size, porosity and pure water flux (PWF). Results showed that the incorporation of IONPs greatly enhanced the membrane PWF from 10.0 L/m2/h to 55.2 L/m2/h, contributed by the enhanced surface hydrophilicity (contact angle = 63.9°), porosity (74.1%) and larger overall pore size (79.3 nm). It was revealed that the membrane possessed phosphate adsorption capacity of 73.5 mg/g. Filtration experiment demonstrated that the PSf/IONPs membrane exhibited efficient phosphate removal under a steady flux. The design of this adsorptive UF membrane could fulfil the current necessity to remove phosphate from wastewater.